2020
DOI: 10.1038/s41598-020-73730-9
|View full text |Cite
|
Sign up to set email alerts
|

A porous collagen-based hydrogel and implantation method for corneal stromal regeneration and sustained local drug delivery

Abstract: Biomaterials designed to replace the diseased cornea could be used to treat corneal blindness where human donor tissue is in short supply, but challenges are the integration of biomaterials with host tissue and cells, avoiding a rapid material degradation and maintaining corneal transparency. Additionally, implantation surgery often triggers an aggressive wound healing response that can lead to corneal thinning and opacity. Here, we report a collagen-based hydrogel with transparency and mechanical properties s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 26 publications
6
46
0
Order By: Relevance
“…6 A exhibited that the cornea was wounded with a customized 3.5-mm vacuum trephine, and then 3D printed cell-laden or cell-free PEGDA-GelMA-20-5 hydrogel was put on the wounded area. Finally, two 8-shaped overlying sutures were used to hold the scaffold in place as reported previously [ 40 ]. During the whole implantation process, the scaffold was robust enough to be handled without collapse.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 A exhibited that the cornea was wounded with a customized 3.5-mm vacuum trephine, and then 3D printed cell-laden or cell-free PEGDA-GelMA-20-5 hydrogel was put on the wounded area. Finally, two 8-shaped overlying sutures were used to hold the scaffold in place as reported previously [ 40 ]. During the whole implantation process, the scaffold was robust enough to be handled without collapse.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the cell-laden or cell-free corneal scaffolds were punched with a trephine and carefully put on the corneal defect area with the printed epithelia layer facing upwards. Considering the risk of tearing the corneal scaffold by suturing, the construct was fixed with two 8-shaped overlying 10-0 sutures as previously reported method [ 40 ]. In the control group, only corneal defect was created and no hydrogel was placed.…”
Section: Methodsmentioning
confidence: 99%
“…Grafting outcomes in mini-pig corneas were superior to those in human subjects, indicating that animal models are only predictive for patients with non-severely pathological corneas ( 120 ). Another method to combat neovascularisation is to integrate a sustained release nanosystem of bevacizumab (an anti-VEGF drug) into the cell-free biosynthetic scaffolds ( 121 ), while ulceration and a neurotrophic deficit could be addressed by sustained release of nerve growth factor, demonstrated recently in a collagen-based scaffold releasing the drug in a controlled manner during a 60-day period ( 122 ).…”
Section: Future Trends For Corneal Implantsmentioning
confidence: 99%
“…For example, carrageenan has been used in different sectors such as drug delivery, packaging, and food additives [28,95,96], whereas cellulose has been studied in drug delivery and textiles [97]. Starch has also been explored in food packaging [98,99]; fibrinogen in drug delivery and wound healing [100,101]; silk in wound healing [102,103]; collagen in tissue engineering [104][105][106] and drug delivery [107][108][109]; pullulan in drug delivery [110], food packaging, and food stabilizing [111,112]; alginate in biomedical applications [113,114]; chitin in tissue engineering [115] and enzyme immobilization [116,117]; and collagen in tissue engineering [104][105][106] and drug delivery [107][108][109]. However, our literature search demonstrated that biopolymers have limited applications in water treatment even though they possess useful properties such as hydrophilicity, an optical nature, and an easy-to-functionalize capacity.…”
Section: Biopolymers' Applicationsmentioning
confidence: 99%